THE ROLE OF INTERPERSONAL COMMUNICATION IN PERSONALITY DEVELOPMENT. (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
In fact, the social experience of each person, his human image, qualities, and even defects are the product of communication processes. A person separated from society, deprived of the opportunity to communicate, can retain the qualities of an individual, but he cannot be a person. Therefore, we analyze its functions in order to imagine the importance of communication in personal development.